Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik Berdasarkan Indeks Kepuasan Masyarakat Di Kantor Wali Nagari Simpang Kapuak, Kecamatan Mungka, Kabupaten Lima Puluh Kota Tahun 2021 - Laura Annisa Fitri; Dewi Dahlan (Politik Islam, 2022)
This study was conducted to determine the level of community satisfaction with services at the Wali Nagari Simpang Kapuak Office, Mungka District, Lima Puluh Kota Regency, measured using the Community Satisfaction Index. This study uses descriptive quantitative-analysis using the Community Satisfaction Index (IKM) analysis in accordance with KEPMENPAN Number 14 of 2017. Data collection techniques are in the form of questionnaires, documentation and observations going into the field with the community with a research sample of 95 people using the simple random sampling method. ). Public services in Nagari Simpang Kapuak include 9 elements of the Community Satisfaction Index including: Requirements; Systems, Mechanisms and Procedures; Service Time; Fees or Tariffs; Product Specification Type of Service; Implementing Competence; Implementing Behavior; Handling of Complaints, Suggestions, and Feedbacks; Facilities and infrastructure. The results showed that the value of the Community Satisfaction Index (IKM) in accordance with KEPMENPAN Number 14 of 2017 for the services of the Simpang Kapuak Wali Nagari Office was running well with an interval value of 3.095 and after being converted to 77.37. So the performance of public services is in the "B" category, which means good